2021
DOI: 10.1029/2020gl091001
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Patterns in the Trades Have Four Interpretable Dimensions

Abstract: Shallow cloud fields over the subtropical ocean exhibit many spatial patterns. The frequency of occurrence of these patterns can change under global warming. Hence, they may influence subtropical marine clouds’ climate feedback. While numerous metrics have been proposed to quantify cloud patterns, a systematic, widely accepted description is still missing. Therefore, this study suggests one. We compute 21 metrics for 5,000 satellite scenes of shallow clouds over the subtropical Atlantic Ocean and translate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…The possible overestimation of the degrees of freedom due to this assumption is compensated for by selecting a very high significance level to ensure statistical robustness. We note that we could have alternatively used the classical Clark‐Evans statistical test (Clark & Evans, 1954 ) directly on sub‐sampled nearest neighbor distances of the velocity field, however, we prefer the application to I org as it is a scene‐integrated quantity that has been widely applied in the field since its introduction (e.g., Bony et al., 2020 ; Brueck et al., 2020 ; Janssens et al., 2021 ; Moseley et al., 2020 ; Pscheidt et al., 2019 ).…”
Section: Model and Methodsmentioning
confidence: 99%
“…The possible overestimation of the degrees of freedom due to this assumption is compensated for by selecting a very high significance level to ensure statistical robustness. We note that we could have alternatively used the classical Clark‐Evans statistical test (Clark & Evans, 1954 ) directly on sub‐sampled nearest neighbor distances of the velocity field, however, we prefer the application to I org as it is a scene‐integrated quantity that has been widely applied in the field since its introduction (e.g., Bony et al., 2020 ; Brueck et al., 2020 ; Janssens et al., 2021 ; Moseley et al., 2020 ; Pscheidt et al., 2019 ).…”
Section: Model and Methodsmentioning
confidence: 99%
“…In contrast to Denby (2020) and Janssens et al (2021) who retrieve a continuum of classes, the limitation to the few categories of Stevens et al (2020) helps to break down natures' complexity into manageable pieces, arguably the building blocks of shallow convection in the downstream trades. Understanding what factors help select these patterns may help understand factors controlling cloudiness as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…During this period, observational studies such as RICO (Rauber et al, 2007) and the emergence of satellite imagery with spatial resolution on the hectometer scale began emphasizing how shallow clouds in the trades adopt different forms of organization, often in association with precipitation development and the formation of cold pools (Seifert & Heus, 2013;Seifert et al, 2015;Zuidema et al, 2012). More recently, several approaches to characterize these forms of organizations have been developed (Denby, 2020;Janssens et al, 2021;Stevens et al, 2020). Stevens et al (2020) identified that most of the largescale patterns of shallow convection can be categorized into four categories, which they called Sugar, Gravel, Flowers, and Fish. Although based solely on the subjective visual inspection of visible satellite imagery in the vicinity of the Barbados Cloud Observatory (BCO), these patterns have varied net cloud radiative effects and thus may influence Earth's climate sensitivity (Bony et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period, observational studies such as RICO (Rauber et al, 2007) and the emergence of satellite imagery with spatial resolution on the hectometer scale began emphasizing how shallow clouds in the trades adopt different forms of organization, often in association with precipitation development and the formation of cold pools (Seifert & Heus, 2013;Seifert et al, 2015;Zuidema et al, 2012). More recently, several approaches to characterize these forms of organizations have been developed (Denby, 2020;Janssens et al, 2021;Stevens et al, 2020). Stevens et al (2020) identified that most of the largescale patterns of shallow convection can be categorized into four categories, which they called Sugar, Gravel, Flowers, and Fish. Although based solely on the subjective visual inspection of visible satellite imagery in the vicinity of the Barbados Cloud Observatory (BCO), these patterns have varied net cloud radiative effects and thus may influence Earth's climate sensitivity (Bony et al, 2020).…”
Section: Introductionmentioning
confidence: 99%